НЕКОТОРЫЕ ТЕОРЕТИКО-ПРАВОВЫЕ ПРОБЛЕМЫ ВЗАИМОДЕЙСТВИЯ ВЫСШИХ ОРГАНОВ ГОСУДАРСТВЕННОЙ ВЛАСТИ В КЫРГЫЗСКОЙ РЕСПУБЛИКЕ (Journal of actual problems of jurisprudence, 2019)
The author, based on the provisions of the Constitution of the Kyrgyz Republic, attempts to give his own interpretation of the interaction ofgovernment branches in the country, noting both positive and negative aspects of functioning and interaction of all branches of government under theConstitution of Kyrgyzstan, 2007.